2020
DOI: 10.1371/journal.pone.0228832
|View full text |Cite
|
Sign up to set email alerts
|

Identifying priority landscapes for conservation of snow leopards in Pakistan

Abstract: Pakistan’s total estimated snow leopard habitat is about 80,000 km2 of which about half is considered prime habitat. However, this preliminary demarcation was not always in close agreement with the actual distribution—the discrepancy may be huge at the local and regional level. Recent technological developments like camera trapping and molecular genetics allow for collecting reliable presence records that could be used to construct realistic species distribution based on empirical data and advanced mathematica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…Snow leopards occur at low densities, which in concert with their elusive nature renders distribution and habitat suitability studies difficult (Ghoshal et al, 2019;Kalashnikova et al, 2019;Watts et al, 2019). Even though studies on snow leopard distribution exist, most of them were conducted in high-quality habitats (Suryawanshi et al, 2019) and are restricted to a few countries such as Pakistan (Hammed et al, 2020), India (Watts et al, 2019;Singh et al, 2020), Nepal (Aryal et al, 2016;Shrestha and Kindlmann, 2020), China (Bai et al, 2018;Li et al, 2020), Southern Russia (Kalashnikova et al, 2019), and Kazakhstan (Holt et al, 2018), whereas in the case of Bhutan, only little is known. Such imbalances in the knowledge of the snow leopard's distribution can result in an incomplete understanding of its distribution nationally and globally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Snow leopards occur at low densities, which in concert with their elusive nature renders distribution and habitat suitability studies difficult (Ghoshal et al, 2019;Kalashnikova et al, 2019;Watts et al, 2019). Even though studies on snow leopard distribution exist, most of them were conducted in high-quality habitats (Suryawanshi et al, 2019) and are restricted to a few countries such as Pakistan (Hammed et al, 2020), India (Watts et al, 2019;Singh et al, 2020), Nepal (Aryal et al, 2016;Shrestha and Kindlmann, 2020), China (Bai et al, 2018;Li et al, 2020), Southern Russia (Kalashnikova et al, 2019), and Kazakhstan (Holt et al, 2018), whereas in the case of Bhutan, only little is known. Such imbalances in the knowledge of the snow leopard's distribution can result in an incomplete understanding of its distribution nationally and globally.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to biophysical factors, bioclimatic factors can also affect snow leopard distribution (Aryal et al, 2016;Bai et al, 2018;Hammed et al, 2020;Shrestha and Kindlmann, 2020). Hence, accounting for them can improve the accuracy of species distribution models (SDMs) (Aryal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent habitat loss leading to fragmentation of the snow leopard's range will present numerous conservation challenges [96]. A recent study confirmed that parts of snow leopard range in Pakistan have very low habitat suitability for the species [49]. However, this may increase as climate change threatens the mountain landscapes that snow leopards are found in.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 24% of the snow leopard habitat is laying inside protected areas of different sizes. According to a recent study [49] most of the suitable habitat of snow leopard in Pakistan has already been protected, however there are some areas presenting suitable habitat are outside of any declared protected area. The same study concluded that most of the national parks had weak links with regards to movement of snow leopard across different habitats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation